2020
DOI: 10.1101/2020.03.13.990572
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Differential brain activity in visuo-perceptual regions during landmark-based navigation in young and healthy older adults

Abstract: 14Older adults exhibit prominent impairments in their capacity to navigate, reorient in 15 unfamiliar environments or update their path when faced with obstacles. This decline in 16 navigational capabilities has traditionally been ascribed to memory impairments and 17 dysexecutive function whereas the impact of visual aging has often been overlooked. The 18 ability to perceive visuo-spatial information such as salient landmarks is essential to navigate 19 in space efficiently. To date, the functional and ne… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 119 publications
(164 reference statements)
0
4
0
Order By: Relevance
“…We thank Konogan Baranton and Isabelle Poulain (Essilor International) for the manufacturing of MRI-compatible glasses. A preliminary version of this manuscript has been released as a pre-print on bioRxiv (Ramanoël et al, 2020 ).…”
mentioning
confidence: 99%
“…We thank Konogan Baranton and Isabelle Poulain (Essilor International) for the manufacturing of MRI-compatible glasses. A preliminary version of this manuscript has been released as a pre-print on bioRxiv (Ramanoël et al, 2020 ).…”
mentioning
confidence: 99%
“…These results have important implications. Extensive literature points to prominent navigational impairments in healthy aging associated with changes in a vast neural network [88][89][90][91]. We revealed that while objects and features can be used equally well to orient in space, object-based navigation is subtended by a more widespread pattern of temporal and occipital activations.…”
Section: Rethinking the Concept Of Landmark In Human Spatial Navigationmentioning
confidence: 83%
“…Spatial frequency content, contrast amplitude, angular size, and position in the visual field may constitute interesting research avenues. Recent studies have revealed that age-related impairments in navigational abilities could be partially explained by the decline of information processing in early visual regions [91,114]. Therefore, specific modulations of these basic visual properties could stabilize or even improve navigation performance ultimately facilitating mobility in normal and pathological aging.…”
Section: Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation